Analisis Dampak Lingkungan Wilayah Pesisir Akibat Tumpahan Oil Spill di Karawang - Annisa, Nur Afif; Vionica, Putri; Kamal, Ubaidillah (Media Hukum Indonesia (MHI), 2024)
Oil spills in the sea have a very bad impact on marine ecosystems. The oil contains dangerous chemicals that can harm marine life. Fish and other marine life absorb these toxic chemicals, which can cause their death and population decline. In addition, oil spills irritate the eyes, skin and respiratory tract and can be fatal. The approach method used is a legal research method that focuses on normative analysis of the law. Naturally, this pollution has an impact on the environment, public health and the economy around Karawang Waters. People are experiencing shortness of breath and headaches due to the smell of the oil spill. The actions carried out by Pertamina are considered a very serious environmental crime. This is because the company encourages fishermen to go straight into the water to handle waste, without involving appropriate professionals, and without providing outreach.